Legal Supervision And Enforcement In Environmental Law Under The Law Number 32 Year 2009 On Environmental And Protection Management - Hery Agus Susanto; Daniel Susilo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2017)
With Law supervision and enforcement in Environmental Law, elements of the environment can be resolved, including elements of conservation, social culture and physical. Element of conservation (biotic) is element of the environment that consists of a living creature, such as a human, animals, plants and microorganisms. Social and Cultural Element is a social-cultural environment created by human beings which is a system of values, ideas and beliefs in behavior as social beings. Physical Elements (abiotic) consists of non-living objects including soil, water, air, climate and other elements. The three elements must be maintained and preserved from environmental damage and pollution. Government is responsible for the welfare of his people and has a fundamental responsibility in realizing the formation of environmental conservation. Protection and Management of law includes Planning, Utilization, Maintenance Controlling, Monitoring and Law Enforcement.